The Clone Wars – Revenge of the Metastatic Rogue State: The Sarcoma Paradigm - Spraker, Holly L.; Price, Shawn; Chaturvedi, Aashi; Schiffman, Joshua D.; Jones, Kevin B.; Lessnick, Stephen; Beckerle, Mary; Randall, R. Lor (Frontiers in Oncology, 2012)
Ewing sarcoma (ES) is the second most common bone tumor affecting primarily adolescents and young adults. Despite recent advances in biological understanding, intensification of chemotherapeutic treatments, and progress in local control with surgery and/or radiation therapy, patients with metastatic or recurrent ES continue to have a dismal prognosis with less than 20% overall survival. All ES likely is metastatic at diagnosis although our methods of detection and classification may not account for this. Progressive disease may arise via a combination of: 1) selection of chemotherapy-resistant clones, 2) signaling from bone or lung microenvironments that may attract tumor cells to distant locations, and/or 3) genetic changes within the ES cells themselves due to a combination of therapy-related selection and DNA-damaging chemotherapeutic agents. These possibilities and the evidence base to support them are explored.